Psalm 119 : the exaltation of Torah - Freedman, David Noel, 1922-2008 (Biblical and Judaic studies, 1999)
From the Preface: "The alphabetic acrostic is one of the most easily identifiable poetic forms in the Hebrew Bible. Examples can be found in prophetic discourse (Nahum), the lament over the destruction of Jerusalem (Lamentations), liturgical song (Psalms), and wisdom literature (Proverbs). Yet its very obviousness has tended to deflect deeper exploration of its structure and purpose. Since Mowinckel denigrated the acrostics in the Psalms as a "disintegration of style,' too often scholars have simply noted and then ignored the form."There is no a priori reason that alphabetic acrostics should be less creative, expressive, or complex than other psalms. Thus the essays collected here investigate the acrostic format as a legitimate option for Israelite poets rather than as the refuge of uninspired epigones.The fruit of over twenty years' close reading of these psalms, the following essays reveal the poets' consummate mastery of the demanding acrostic form and deserve incorporation in future discussions of biblical poetic art.